The integration strategies and social networks of Somali women in Cape Town - Brown, Parveen (Department of Sociology, 2015)
Somali migrants began arriving in the country in the early 1990’s, following the collapse of the state in Somalia and the promise of increased opportunities in South Africa. This study is based on the experiences of Somali women in Bellville, which is situated in Cape Town; it is home to one of the largest Somali community’s in the country. Migration to South Africa has brought Somali women into a new gendered context which has provided the opportunity to renegotiate gendered roles and practices. I focus on gendered processes of integration and adaptation to South Africa. The study also investigates how different forms of social networks influence integration and the kinds of value systems and identities that are reproduced through these networks. People experience migration and resettlement in gendered ways. Postcolonial feminist theory and the gendered geographies of power framework are used as tools to analyse how gender operates in the new migratory context. Social network theory is used to gain insight into the functions and features of networks among migrant women. The study takes an inductive approach and employs a qualitative research strategy. In-depth individual interviews and group discussions were conducted with 13 women migrants and 4 individuals from organisations working closely with the Somali community of Cape Town. Women’s experiences reveal varying degrees, to which they accept, resist or negotiate different gendered norms. The ability of Somali women to insert their own gendered norms into existing societal patterns disrupts dominant discourses. The integration strategies migrants adopt are influenced by the kinds of social networks which are dominant in their lives. As expected this study finds that migrants draw on kin based networks where they choose to remain strongly connected to the Somali community. These networks can be restrictive in that they pressure migrants to conform to group expectations and norms; but they are also important as a source of social and economic support. Some migrants operate within a broader social network, linked not only to the Somali community but also to the broader South African society. These migrants have a stronger socio-economic position compared to the others which enables them to move beyond kin based networks more easily as they are not as dependent on these networks to integrate.